2004
DOI: 10.1074/jbc.m311367200
|View full text |Cite
|
Sign up to set email alerts
|

The Predicted TM10 Transmembrane Sequence of the Cardiac Ca2+ Release Channel (Ryanodine Receptor) Is Crucial for Channel Activation and Gating

Abstract: The predicted TM10 transmembrane sequence, 4844 IIFDITFFFFVIVILLAIIQGLII 4867 , has been proposed to be the pore inner helix of the ryanodine receptor (RyR) and to play a crucial role in channel activation and gating, as with the inner helix of bacterial potassium channels. However, experimental evidence for the involvement of the TM10 sequence in RyR channel activation and gating is lacking. In the present study, we have systematically investigated the effects of mutations of each residue within the 24-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…1). These structural features are consistent with our previous functional studies demonstrating the critical role of the S6 helix bundle crossing region in the regulation and gating of RyR2 (25)(26)(27)(28)(29). However, the functional significance of the C-terminal (cytoplasmic) region of the S6 inner helix is unknown.…”
Section: Discussionsupporting
confidence: 80%
“…1). These structural features are consistent with our previous functional studies demonstrating the critical role of the S6 helix bundle crossing region in the regulation and gating of RyR2 (25)(26)(27)(28)(29). However, the functional significance of the C-terminal (cytoplasmic) region of the S6 inner helix is unknown.…”
Section: Discussionsupporting
confidence: 80%
“…The deletion was identified as a novel mutation in one patient (17). Wang et al (33,34) mutated the residues within the membrane-spanning segment of the cardiac ryanodine receptor (RyR2) to alanine and found that RyR2-V4854A and -I4855A (matching RyR1-V4926 and -I4927 deletion sites) retained function but showed a reduced response to caffeine activation. We previously showed that deletion of RyR1 residues Val-4926 and Ile-4927 results in a nonfunctional channel unable to conduct Ca 2ϩ (19).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of more substantial data in this area begs for additional experimental effort. A number of mutations in the pore region of the RyR have either been described (central core disease mutations) or engineered (114,116,117,155,217,304,500,501,504,522,524,546). The pore region of the cardiac RyR2 channel has been modeled onto the KcsA pore structure (507).…”
Section: F Molecular Models Of the Insp 3 R Porementioning
confidence: 99%